PENGARUH KOMBINASI HIDROTERAPI DAN METODE INHALASI AROMATHERAPY NEROLI TERHADAP PENURUNAN HIPERTENSI PADA KEHAMILAN - Nanda Mirani (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2022)
Hypertensive disorders are a common complication of pregnancy that put women and their fetuses at disproportionate risk for further complications, as well as life-long sequelae. Hypertensive disorders of pregnancy affect up to 10% of pregnancies worldwide, which includes the 3%–5% of all pregnancies complicated by preeclampsia. The purpose of this study was to determine the effect of the combination of hydrotherapy and the inhalation method of neroli aromatherapy on reducing blood pressure in pregnant women. This study uses a quasi-experimental method with a one-group pre-test and post-test design approach. The sample involved was 16 people who were selected using purposive sampling technique. Data analysis was carried out univariate and bivariate using the paired T-Test. The results showed that there was an effect of the combination of hydrotherapy and the inhalation method of neroli aromatherapy on reducing systolic and diastolic blood pressure in pregnant women. The combination of hydrotherapy and administration of neroli aromatherapy with the inhalation method can reduce systolic and diastolic blood pressure, making it an effective alternative to non-pharmacological therapy for hypertensive patients, especially pregnant women.